A Rare Case of Posterior Tibial Artery Hypoplasia and Fibular Artery Enlargement and their Impact on the Arterial Supply of Posterior Crural Region - Maria Piagkou; Stylianos Kapetanakis; George Tsakotos; Alexandros Samolis; Nikolaos Anastasopoulos; Konstantinos Natsis (Folia Medica, 2019)
Background: Detailed knowledge of the popliteal artery division and possible anatomical variants is of paramount importance for vascular surgery.Aim: The aim of the current study was to highlight a rare unilateral case of posterior tibial artery hypoplasia.Materials and methods: A dissection was performed at the posterior surface of the tibia in a 78-year-old Caucasian male cadaver of Greek origin.Results: The findings were consistent with unilateral posterior tibial artery hypoplasia and fibular artery enlargement. The variant fibular artery supplied the posterior surface of the distal leg and foot. Clinical implications of the fibular artery dominance are discussed.Conclusions: Rare anatomical variants of the tibial artery are of clinical significance to maximize safety and minimize intraoperative complications.